Empowering citizen media through investigative journalism in Malaysia - Norsiah Abdul Hamid; Mohd Sobhi Ishak; Nazialita Geynna Maharan (Pusat Pengajian Media dan Komunikasi, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2015)
Investigative journalism nowadays plays a crucial role in the democratization of a nation. This paper discusses a study conducted to examine the challenges of investigative journalism in Malaysia, the significance of journalism ethics and rules in Malaysia in the investigative journalism practices, and to suggest and recommend the ways and method to handle any future challenges in the investigative journalism world. The study employed a qualitative method in which an in-depth interview was carried out with three investigative journalism experts in Malaysia. The subjects were carefully selected through purposive sampling. In addition, the interview questions were constructed based on data collected from document analysis. It is important to gain an initial data on investigative journalism in Malaysia. Three main themes selected for the studies are communication, empowerment and governance. The incorporation and collaboration between these three themes influenced and moulded the practices of investigative journalism in the country. Results revealed that there are similar and different traits of investigative journalism practices in Malaysia. For the alternative media, passion is a must in coming down as a journalist and try to take a more courageous act in telling and serving truth to the public. Investigative journalism can continue to exist in the world of ubiquitous media and information overloaded.